MOTIVASI IBU HAMIL TENTANG KEBERSIHAN GIGI DAN MULUT DI PUSKESMAS NGUMPAKDALEM BOJONEGORO - sintya malra nur fitriana; Ida Chairanna Mahirawatie; Agus Marjianto (Politeknik Kementerian Kesehatan Banjarmasin, 2021)
The problem with this study is that the percentage of caries of pregnant mothers' teeth at the Ngumpakdalem center Dander Bojonegoro district 60,94% of free targets karies 54.6%. The purpose of the study discovered mom's motivation for oral hygiene in the Ngumdalem Hospital District Dander Bojonegoro. A descriptive method of research. The targets involved in this study are 30 expectant mothers who are 20-30 years of age. Instruments used in Research is a questionnaire. Studies have shown that mothers' motivation for oral hygiene in the medical center is pure Ngumpakdalem district Dander Bojonegoro year in Strong category. The conclusion that the expectant mother already had the motivation to keep her teeth and mouth clean. Keywords: motivation, hygiene and oral hygiene, the mother is pregnant